District level decoupling analysis of energy-related carbon dioxide emissions from economic growth in Beijing, China - Baoguo Shi; Wenjing Xiang; Xiaodan Bai; Yanjie Wang; Guihong Geng; Ji Zheng (Energy Reports, 2022)
Energy-related CO2 emissions are mainly concentrated in urban areas. Quantitative research on the relationship between CO2 emissions and economic growth at city and sub-city level is of great importance. Based on the Tapio’s decoupling model, this paper analyzes the decoupling status of CO2 emissions from economic growth in the 16 districts of Beijing during the period of 2006–2017. The decoupling state of the 16 districts showed obvious phased improvement characteristics. In 2017, 93.75% districts achieved decoupling state, including strong decoupling and weak decoupling, of CO2 emissions from economic growth and 37.50% districts achieve strong decoupling, the most desirable decoupling state. The effect of urban functional zoning and industrial structure transition on the total CO2 emissions and the direct influences of the national environmental protection policies and big public event on the decoupling of CO2 emissions from economic growth were observed. This study will enrich the body of decoupling research at the district level and will provide scientific support to the achievement of the “double carbon” target in Beijing and other Chinese cities.